In Situ Real‐Time Nanoscale Resolution of Structural Evolution and Dynamics of Fluorescent Self‐Assemblies by Super‐Resolution Imaging. Issue 34 (14th July 2022) - Qiao, Qinglong; Liu, Wenjuan; Zhang, Yinchan; Chen, Jie; Wang, Guangying; Tao, Yi; Miao, Lu; Jiang, Wenchao; An, Kai; Xu, Zhaochao
Abstract: The visualization of self‐assembled structure and dynamics at the molecular level has become a powerful method to understand structure–function relationships of self‐assembly. Herein, we in situ real‐time imaged the dynamic process of benzyl‐naphthalimide dyes at the nanoscale and inspected their internal structure with minimum 2.8 nm localization accuracy through single‐molecule localization microscopy (SMLM) imaging. We monitored the growth process of three different assemblies in situ, which possessed highly heterogeneous dynamics with different shapes and growth rates. Furthermore, diverse growth rates were also found at different sites in the same assembly. These results highlight the application of super‐resolution microscopy techniques for real‐time visualization of internal assembled structure and dynamics in situ. Abstract : In situ real‐time imaging of the dynamic process of benzyl‐naphthalimide dyes at the nanoscale was performed and their internal structures were inspected with minimum 2.8 nm localization accuracy through single‐molecule localization microscopy (SMLM) imaging. This revealed the heterogeneity and dynamics of the three different assemblies in situ.